2010
DOI: 10.1121/1.3372730
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in children’s singing voices: Acoustic analyses and results of a listening test

Abstract: This study tested the hypothesis that acoustic parameters exist which are specific to gender in children's singing voices, and that these parameters are relevant to listeners' identification of gender of children's singing voices. A listening test was run with examples of singing produced by children belonging to different singing cultures, six boys and six girls from a Swedish music school and six boys from an elite German boys' choir. Sustained vowels were analyzed with regard to formants and voice source pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Indeed, Shue (2010) found that voice measures can improve automatic sex classification, though significantly so only for 10-to-14-year-old children's voices. Similarly, Mecke and Sundberg (2010) found that listeners' judgments of the sex of 10-to-13-year-old singing children correlated well with the Closed Quotient from electroglottographic signals. However, vowel F4 correlated best, and F2, F3 and F5 were also correlated with the responses, suggesting that listeners use vocal tract information more than voice quality information in this decision.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, Shue (2010) found that voice measures can improve automatic sex classification, though significantly so only for 10-to-14-year-old children's voices. Similarly, Mecke and Sundberg (2010) found that listeners' judgments of the sex of 10-to-13-year-old singing children correlated well with the Closed Quotient from electroglottographic signals. However, vowel F4 correlated best, and F2, F3 and F5 were also correlated with the responses, suggesting that listeners use vocal tract information more than voice quality information in this decision.…”
Section: Introductionmentioning
confidence: 89%
“…For example, boys tend to present vocal hyperfunctionality with greater respiratory intake for more intense voice production, while girls show more breathiness (17)(18)(19) . Although these data are observed in the clinical setting as well as the studies cited, there is no consensus regarding children's voices; some authors do not confirm a higher occurrence of breathiness in girls' voices when compared to boys' voices in the same choir (20) .…”
Section: Discussionmentioning
confidence: 89%
“…Johan Sundberg has published over 300 journal articles (not including technical papers produced in house at KTH). These articles touch on an enormous variety of topics from basic music acoustics to such areas as the sensitivity of musicians to cues of depression reflected in the voice (Nilsonne & Sundberg, 1985), the acoustics of barbershop singing (Hagerman & Sundberg, 1980), child singers (McAllister, Sederholm, & Sundberg, 1994;Mecke & Sundberg, 2010), older singers (Sundberg, Niska-Thörnvik, & Söderström, 1998), opera singers (Echternach, Sundberg, Baumann, Markl, & Richter, 2011), music-theatre singers (Sundberg, Thalén, & Popeil, 2010), and country singers (Stone, Cleveland, & Sundberg, 1999) as only some examples. Other research deals with the synthesis of the singing voice from vowels to the emotional aspects (Sundberg, 1988(Sundberg, , 1989Sundberg, Askenfelt, & Frydén, 1983).…”
Section: Ac a De M Ic Ac T I V I T I E S And Pu Bl Ic At Ion Smentioning
confidence: 99%